Pengaruh Pendidikan Kesehatan dengan Lembar Balik Terhadap Perilaku Pemberian Asi pada Ibu Post Partum: The Effect of Health Education with Flipcharts on Breastfeeding Behavior in Post Partum Mothers - Maulida, Luluk Fajria (Jurnal Kebidanan Midwiferia, 2017)
One of the obstacles in breastfeeding attitude is the lack of lactation communication and counseling. Breastfeeding health education is designed to enforce healthy lifestyle of breastfeeding by delivering proof based information. Flipchart media usage can be easily understood by health counsellors and clients. The study is to investigate the influence of health education using flipchart over breastfeeding attitude in post-partum mothers. This research was used a quasi experiment design with posttest only design with control group. A random assignment sampling design was used to 42 respondents which were divided into 2 groups; intervention group and control group. The samples were randomized using numbers and were divided into intervention and control group. The intervention group was given health education after delivery and questionnaires were given in intervention and control group a week after postpartum. The average score postpartum maternal behavior in the intervention group (18,43) is higher than the control group (15,14). The results of chi square test p = 0.00; RR = 3.16; CI = 1,58-6,31. External variables related to the behavior of breastfeeding is the education level of p = 0.02. Health education using flipchart significantly affects breastfeeding behavior in postpartum mothers.